Prevention of oxaliplatin-induced peripheral neuropathy by a polyamine-reduced diet—NEUROXAPOL: protocol of a prospective, randomised, controlled, single-blind and monocentric trial. Issue 4 (1st April 2015) - Balayssac, David; Ferrier, Jérémy; Pereira, Bruno; Gillet, Brigitte; Pétorin, Caroline; Vein, Julie; Libert, Frédéric; Eschalier, Alain; Pezet, Denis
Abstract : Introduction: Oxaliplatin remains the most widely used chemotherapeutic agent for treating advanced colorectal cancer but its efficacy is hampered by dose-limiting neurotoxicity manifested by a painful polyneuropathy. Oxaliplatin-induced peripheral neuropathy (OIPN) is characterised by acute and transient cold hyperaesthesia in the hours and days following oxaliplatin infusion (>90% of patients), but also by retarded chronic neuropathy due to the repetition of chemotherapy cycles (30–50% of patients). OIPN impairs the health-related quality of life (HRQOL) of patients and no preventive or curative strategies have as yet proven effective. A polyamine-reduced diet (PRD) has recently demonstrated its efficacy to prevent OIPN in animals without adverse effects. Methods and analysis: The NEUROXAPOL trial is a prospective, randomised, controlled, single-blind, monocentric and interventional study. This trial is aimed at evaluating the efficacy and feasibility of a PRD compared to a normal polyamine containing diet to prevent OIPN in patients treated by oxaliplatin-based chemotherapy. Patients (n=40 per group) will be randomly assigned to receive either a PRD or a normal diet before and during the chemotherapy regimen. The main objectives are to improve the cold pain thresholds, neuropathic pain symptoms, comorbidities (anxiety and depression) and HRQOL of patients. The primary end point is the assessment of cold pain thresholds 2 weeks after the third cycle of chemotherapy. The secondary end points are the evaluation of thermal pain thresholds, the grade of neuropathy, neuropathic pain, symptoms of anxiety and depression and HRQOL, until the 12th cycle of chemotherapy. Ethics and dissemination: The study was approved by an independent medical ethics committee 1 (CPP Sud Est 1, Saint Etienne, France) and registered by the competent French authority (ANSM, Saint Denis, France). The results will be disseminated in a peer-reviewed journal and presented at international congresses. Trial registration number: NCT01775449.